2011
DOI: 10.3109/0284186x.2011.633928
|View full text |Cite
|
Sign up to set email alerts
|

Survival for colon and rectal cancer in Estonia: Role of staging and treatment

Abstract: Background. International comparisons have indicated low colorectal cancer (CRC) survival in Estonia, compared to other European countries. The objective of this paper is to analyse long-term survival as well as staging and treatment patterns of CRC in Estonia. Material and methods. The analysis included all incident cases of CRC diagnosed in Estonia in 1997 (n ϭ 546), identifi ed through the Estonian Cancer Registry and followed up for 10 years after diagnosis. Staging and treatment data were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…These trends are likely to be attributable to earlier diagnosis, reduction in postoperative mortality, 52 and more effective treatment. 53,54 For rectal cancer, preoperative radiotherapy and total mesorectal excision reduce local recurrence and extend survival, 5557 which could account for improvements noted in Canada, Finland, the Netherlands, Norway, Sweden, and the USA, where survival was already high (55–60%) for patients diagnosed in 1995–99 and rose further for those diagnosed during 2005–09 (62–65%). These trends accord with those reported from the Netherlands, 58 Scotland, the Nordic countries, 59 and elsewhere in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…These trends are likely to be attributable to earlier diagnosis, reduction in postoperative mortality, 52 and more effective treatment. 53,54 For rectal cancer, preoperative radiotherapy and total mesorectal excision reduce local recurrence and extend survival, 5557 which could account for improvements noted in Canada, Finland, the Netherlands, Norway, Sweden, and the USA, where survival was already high (55–60%) for patients diagnosed in 1995–99 and rose further for those diagnosed during 2005–09 (62–65%). These trends accord with those reported from the Netherlands, 58 Scotland, the Nordic countries, 59 and elsewhere in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings from MNCR in the period between 2008 and 2009 also reported that patients diagnosed with stage IV had the highest risk of death compared to patients with earlier stages ( 13 ). In Estonia, patients with advanced stages of colon and rectal cancers have poor 5-year survival rates of 2% and 4%, respectively ( 38 ). Similarly, the relative survival at 5 years was 9% among those with late-stage diagnosis in Mumbai, India ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…6 A more detailed analysis of the 1997 Estonian CRC cohort showed extremely low quality of pathological examination, inadequate staging and insufficient use of neoadjuvant and adjuvant therapies. 7 A recent analysis of Estonian Cancer Registry data demonstrated that both overall Strengths and limitations of this study ► A population-based sample drawn from the nationwide cancer registry. ► Uniform data gathering from patient records by specialised doctors according to EUROCARE High-Resolution study protocols and ability to directly compare two incidence years.…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed analysis of the 1997 Estonian CRC cohort showed extremely low quality of pathological examination, inadequate staging and insufficient use of neoadjuvant and adjuvant therapies. 7 …”
Section: Introductionmentioning
confidence: 99%